FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN MODA TRANSPORTASI PARIWISATA PT. TUNAS ANTARNUSA MUDA WISATA DI KOTA PEKANBARU - Putra, Dawendra; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
PT. Tunas Antarnusa Muda Wisata is one of the tourism transportation modes in the city of Pekanbaru. Formerly a small business, PT. Tunas Antarnusa Muda Wisata has grown to become one of the best tourism transportation modes in Pekanbaru, providing excellent service, well-equipped bus units, and utillzing the lates technology in today’s tourism transportation industry. Therefore, this research is conducted to determine the factors influencing the selection of PT. Tunas Antarnusa Muda Wisata as a tourism transportation in Pekanbaru. This study uses a quantitative descriptive method by distributing questionnaires via google form and directly to 88 respondents using a likert scale. The data collection techniques in this study include observation, interview, questionnaires, and documentation. Based on the data management result using the likert scale measurement technique, factors influencing the selection of PT. Tunas Antarnusa Muda Wisata tourism transportation in Pekanbaru are accessibility and comfort, time and distance, transportation costs, and infrastructure and transportation system development. The score for accessibility and comfort factors is 731, the score for time and distance factors is 723. The score for transportation costs factors is 709, and the score for infrastructure and transportation system development factors is 694, with the most dominant factor being accessibility and comfort. Based on the questionnaire result, the respondent profile indicates that the majority of respondent are male in the 17-25 age group, with their tourism destinations mostly in North Sumatera, and they have purchased PT. Tunas Antarnusa Muda Wisata tourism transportation service once. Keywords : Tourism, Mode Selection, Tourism Transportation Mode, PT. Tunas Antarnusa Muda Wisata